Improving the fidelity of Thermus thermophilus DNA ligase. - Luo, J (1996)
The DNA ligase from Thermus thermophilus (Tth DNA ligase) seals single-strand breaks (nicks) in DNA duplex substrates. The specificity and thermostability of this enzyme are exploited in the ligase chain reaction (LCR) and ligase detection reaction (LDR) to distinguish single base mutations associated with genetic diseases. Herein, we describe a quantitative assay using fluorescently labeled substrates to study the fidelity of Tth DNA ligase. The enzyme exhibits significantly greater discrimination against all single base mismatches on the 3'-side of the nick in comparison with those on the 5'-side of the nick. Among all 12 possible single base pair mismatches on the 3'-side of the nick, only T-G and G-T mismatches generated a quantifiable level of ligation products after 23 h incubation. The high fidelity of Tth DNA ligase can be improved further by introducing a mismatched base or a universal nucleoside analog at the third position of the discriminating oligonucleotide. Finally, two mutant Tth DNA ligases, K294R and K294P, were found to have increased fidelity using this assay.